Exploring the contextual factors, behaviour change techniques, barriers and facilitators of interventions to improve oral health in people with severe mental illness: A qualitative study - Mishu, Masuma Pervin; Faisal, Mehreen Riaz; Macnamara, Alexandra; Sabbah, Wael; Peckham, Emily; Newbronner, Liz; Gilbody, Simon; Gega, Lina (Frontiers in Psychiatry, 2022)
People with severe mental illness (SMI) have significantly poorer oral health compared to people without SMI and interventions targeted to improve oral health in this population failed to show any long-term improvement. Interventions are influenced by many contextual factors ranging from individual to systems level. This study aimed to understand the contextual factors, behaviour change techniques of the available oral health interventions and explore the barriers to and facilitators for engagement with these interventions from the perspectives of people with SMI (service users) and related service providers. Intervention details were extracted from 12 intervention studies identified from a previous systematic review using the template for intervention description and replication checklist (TIDieR) and behaviour change techniques (BCTs) were coded using the behaviour change technique taxonomy v1. Twelve individual BCTs were identified and out of which ‘3.1 instructions on how to perform the behaviour’ (n=8) and ‘4.1 demonstration of behaviour’ (n= 6) were most frequently used BCTs. Video vignettes prepared from the different intervention components identified from existing studies were shown to service users and service providers in dyadic or one-to-one interview format to elicit their views on barriers and facilitators for engagement with the intervention components. Interviews were analysed using Framework analysis and were guided by theoretical domains framework (TDF); and capability, opportunity and motivation (COM-B) model of behaviour change. Main facilitators identified to increase capability, opportunity and motivation of service users were the involvement of carers/care coordinators and integration of dental and mental health care, provision of oral health/hygiene information/products at an appropriate level and provision of tailored support according to individual needs and preferences. Barriers identified were related to lack of communication skills of the service providers, provision of coordinated care, lack of support in visiting a dentist and navigating the payment system and long follow up times. Appropriate training was considered as a facilitator, and staff turnovers and workload were considered as main barriers by the service providers. The findings suggest that comprehensive interventions that target barriers and enhance facilitators from individual to systems level are needed to improve oral health outcomes of people with SMI.